Identifikasi Intrusi Air Laut Menggunakan Metode Geolistrik Di Desa Kampung Baru, Tanah Bumbu - Puji Astutik; Sri Cahyo Wahyono; Simon Sadok Siregar (Lambung Mangkurat University Press, 2016)
Society of Kampung Baru village living in coastal areas utilize ground water to filling the need of ground water consumption. Over take of Ground water made different between ground water level and sea surface level so get seawater intrusion. Therefore, research has done to knowing depth value of distribution by resistiviting value and well water of NaCl contents in Kampung Baru village. Based on result of geoelectric data processing 2D Wenner configuration on 3 tracks with each tracks length 200m which made by Res2dinv software, then sea intrusion start from 0.93-19.6 m with resistivity value 0.2-6.40 Ωm. Based on the result of laboratory tests on three sample showed levels ranging Na is 12,055-14,027 mg/l and Cl has a value that ranges between 52,18-94,58 mg/l. Where this value is below the maximum levels that may be consumed